Antisense Oligonucleotide Therapy for Neurodevelopmental Disorders - Hill, Sophie F; Meisler, Miriam H (Developmental neuroscience, 2021)
Antisense oligonucleotides (ASOs) are short oligonucleotides that can modify gene expression and mRNA splicing in the nervous system. The FDA has approved ASOs for treatment of ten genetic disorders, with many applications currently in the pipeline. We describe the molecular mechanisms of ASO treatment for four neurodevelopmental and neuromuscular disorders. The ASO nusinersen is a general treatment for mutations of SMN1 in spinal muscular atrophy that corrects the splicing defect in the SMN2 gene. Milasen is a patient-specific ASO that rescues splicing of CNL7 in Batten's disease. STK-001 is an ASO that increases expression of the sodium channel gene SCN1A by exclusion of a poison exon. An ASO that reduces the abundance of the SCN8A mRNA is therapeutic in mouse models of developmental and epileptic encephalopathy. These examples demonstrate the variety of mechanisms and range of applications of ASOs for treatment of neurodevelopmental disorders.